Plasma lactate concentrations for self-selected maximal effort lasting 1 h - Myburgh, K. H.; Viljoen, A.; Tereblanche, S. (Medicine & Science in Sports & Exercise, 1998)
PURPOSE: We determined the plasma lactate concentrations for 11 well-trained endurance cyclists or triathletes during a laboratory trial to measure maximal distance cycled in 1 h. METHODS: Subjects performed three distance trials, cycling as far as possible in 1 h. Blood samples were taken from a forearm vein every 10 min during the third trial (T). Samples were analyzed by spectrophotometer for plasma lactate concentrations ([La]). RESULTS: During T, subjects cycled 40.8+/-2.2 km at an average of 83+/-4% of their predicted maximum heart rate (HRmax). Minimum and maximum [La] for each subject was noted for minutes 10, 20, 30, 40, and 50. Minimum [La] ranged between 2.8 and 10.3 mmol x L(-1), and maximum [La] ranged between 5.8 and 13.6 mmol x L(-1). The average [La] from minute 10 to 50 was calculated for each subject and ranged from 5.0 to 12.3 mmol x L(-1). This did not correlate with performance (distance covered in 1 h). Therefore, there was a wide range of individual plasma lactate responses to the same laboratory test that simulated an actual race. The overall average [La] for all subjects was 7.6+/-2.1 mmol x L(-1). CONCLUSIONS: These data indicate first that the value of 4 mmol x L(-1), commonly referred to as OBLA, may often underestimate the upper limit of tolerance to lactate during a maximal endurance performance test lasting approximately 1 h. Second, during this type of work, intersubject differences in average plasma lactate concentration do not correlate with performance.